Perbedaan Saham Blue Chip dan Non Blue Chip: Analisis Volume Perdagangan dan Return Saham Atas Kebijakan Stock Split - Akhmad, Irfan Maulana; Damayanti, Cacik Rut (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2021)
The stock split phenomenon is still challenging to understand the returns to companies and investors. A stock split is a corporate actions to break up more shares so that the price per share changes to a smaller one, which aims to increase stock liquidity. The purpose of this study is to analyze differences in trading volume, and stock returns before and after the company's stock split policy implemented in blue-chip and non blue-chip Indonesian companies in the 2017-2019 period, amounting to 34 companies. This study uses data analysis techniques in the Wilcoxon Signed Ranks Test and the Mann-Whitney T-Test. The results showed a significant difference to the average trading volume, but there was no significant difference to the average stock return before and after the stock split policy. The test results of the average difference between blue chip and non blue-chip companies have no significant differences. The company's market capitalization has no significant effect on stock returns and trading volume in the stock split period. The results of this study can be used as reference material for investors and companies in making decisions.